Evaluation of Aerated Drilling in K-01 Geothermal Well using Guo Ghalambor’s Gas-Liquid Rate Window - Raka Sudira Wardana; Khansa Rasyidah (PETRO:Jurnal Ilmiah Teknik Perminyakan, 2020)
Common problem in geothermal drilling is loss circulation problem. One of the common methods to cure loss circulation problem is using Lost Circulation Materials (LCM), but in the production zone, using LCM can damage the production zone. Therefore, underbalanced drilling is method that can be used to prevent loss circulation problems in production zone in geothermal well. One of the most common underbalanced drilling methods is aerated drilling or foam drilling. Aerated drilling was used to overcome the loss of circulation problem in production zone in K-01 Geothermal Well. Even though, the aerated drilling was already used, but the loss circulation problem was still occurred. The purpose of this research is to evaluate aerated drilling operation in K-01 Well using Guo Ghalambor’s Gas-Liquid Rate Window and make recommended gas-liquid rate for the next drilling operation. Gas-Liquid Rate Window is constructed using characteristic of the formation, drilling parameters, daily drilling report and also fluid injection characteristics that was used for aerated drilling operation in K-01 geothermal well. Using the constructed Gas-Liquid Rate Window, an evaluation is carried out for the drilling operation in K-01 geothermal well.  The gas-liquid rate parameters used in aerated drilling operations is evaluated while checking the loss circulation event from the mud logging data. After the evaluation of the aerated drilling is carried out in then a suggestion is made for the next drilling operation. Based on the evaluation, the combination of gas-liquid rates that was used on the 9.875"hole section in K-01 Well was in the outside of the constructed GLRW therefore loss circulation problem occurred. The recommended gas-liquid rate combination from this research can be used to determine the gas-liquid rate combination to prevent loss circulation problems, wellbore damage and cutting transport problems.